Use of artificial primary teeth for endodontic laboratory research: experiments related to canal length determination - Anna Carolina V. Mello-Moura; Carmela R. Bresolin; Cacio Moura-Netto; André Ito; Angela T. Araki; José Carlos P. Imparato; Fausto M. Mendes (BMC, 2017)
Abstract Background Due to the scarcity of exfoliated/extracted human primary teeth with complete roots, artificial teeth were developed as an alternative to be used for educational and laboratory research purposes. This study aimed to assess the feasibility of using artificial primary teeth for conducting laboratory research through an experiment related to canal length determination, comparing artificial teeth with natural teeth. Methods Thirty anterior and 21 posterior artificial teeth, and the same number of natural primary teeth were selected. After preparing the access cavity, the root canal length was determined by two examiners twice using three different methods: radiography and two electronic apex locators. Then, the actual root canal length was measured by inserting a K-file up to the apical foramen (reference standard). Accuracy was calculated using Bland-Altman analysis and intraclass correlation coefficient (ICC). The inter- and intra-examiner reproducibility was also calculated using the ICC. Results The methods using the electronic apex locators showed better accuracy in both artificial and natural teeth. Trends observed with artificial primary teeth were similar to those observed with natural teeth, except for the results in artificial anterior teeth. Conclusions The model of artificial teeth might be a good alternative for educational purposes; however, improvements are necessary to employ these teeth for research purposes when considering experiments for canal length determination.